2011
DOI: 10.4141/cjps2011-002
|View full text |Cite
|
Sign up to set email alerts
|

Alternative oilseed crops for biodiesel feedstock on the Canadian prairies

Abstract: Blackshaw, R. E., Johnson, E. N., Gan, Y., May, W. E., McAndrew, D. W., Barthet, V., McDonald, T. and Wispinski, D. 2011. Alternative oilseed crops for biodiesel feedstock on the Canadian prairies. Can. J. Plant Sci. 91: 889–896. Increased demand for biodiesel feedstock has encouraged greater napus canola (Brassica napus L.) production, but there may be a need for greater production of other oilseed crops for this purpose. A multi-site field study was conducted to determine the oil yield potential of various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 29 publications
6
78
1
Order By: Relevance
“…Research on B. carinata has shown that it can compete yield-wise with B. napus while producing industrial quality oil rather than that for food use (Pan et al, 2012). Likewise, S. alba is well adapted to cool short-season environments and has been considered as a potential feedstock for advanced biofuels (Blackshaw et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on B. carinata has shown that it can compete yield-wise with B. napus while producing industrial quality oil rather than that for food use (Pan et al, 2012). Likewise, S. alba is well adapted to cool short-season environments and has been considered as a potential feedstock for advanced biofuels (Blackshaw et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Camelina has a relatively short growing season (85e100 days), and possesses winter and spring varieties, facilitating rotation with other crops [6]. Further, the oil yield of Camelina (variable from 400 to 850 kg ha À1 , depending on the study) is typically comparable with that of Brassica juncea and Brassica rapa and higher than that of soybean [6,7]. While the oil yield is somewhat lower than that of canola, studies have shown that the cost of production of seed oil from Camelina can be less than half that from rapeseed due to comparatively low input requirements [8].…”
Section: Agronomic Advantages Of Camelinamentioning
confidence: 99%
“…Attention has been given to Camelina sativa, which has yielded around 550 kg of seed ha −1 following winter wheat without fallow under normal annual precipitation levels of 240 mm at Lind, WA [124], and yielded 639 kg ha −1 following durum in a 5-year study near Froid, MT, that had average annual precipitation that ranged from 338 to 524 mm [4]. Camelina is best adapted to cooler climates where excessive heat during flowering does not occur [21]. The potential for Brassica carinata as an oilseed crop for warmer, drier areas of western Canada was identified by Taylor et al [133].…”
Section: Fertilitymentioning
confidence: 99%